AFTER THE ENLIGHTENMENT: THE REDISCOVERY OF AVERROES BY TIEDEMANN AND HERDER. Issue 1 (March 2023) - Schick, Stefan
Abstract: Both Arabic modernists and Western humanists often regard the Muslim philosopher Averroes as one of the earliest precursors of Kant and the European Enlightenment. In contrast to this reputation, this paper argues that it was Kant's critics Herder and Tiedemann who rediscovered Averroes. Tiedemann was the first German historiographer to give an accurate account of Averroes' thought. This was accompanied by a re-evaluation of Averroes by Herder in his Letters for the Advancement of Humanity, in which he recognized the similarity between his own concept of the spirit of the age as historical reason – his alternative to the Enlightenment concept of a universal and ahistorical reason – and Averroes' concept of a single material intellect for all individual human minds. Finally, the paper outlines the possible connections between Averroes' interpretation of Aristotle's intellect and Hegel's concept of reason in history.